Enviromagnetic study of Late Quaternary environmental evolution in Lower Volga loess sequences, Russia. (September 2021) - Költringer, Chiara; Stevens, Thomas; Bradák, Balázs; Almqvist, Bjarne; Kurbanov, Redzhep; Snowball, Ian; Yarovaya, Sofya
Abstract: The late Quaternary development of the Lower Volga region of Russia is characterized by an alternating influence of marine and continental environments resulting from fluctuations in Caspian Sea level during the last glaciation. However, sediments deposited under continental conditions have received very little research attention compared to the under- and overlying marine deposits, such that even their origin is still in debate. Detailed magnetic mineralogical analyses presented here show clear similarities to loess. The results suggest that climate during the time of loess deposition, the Atelian regression (27–80 ka, MIS 4–3), was dry and cool, similar to the modern-day Northern Caspian lowland. The magnetic properties recorded in the loess-paleosol sequences of the Lower Volga also point to short episodes of potentially more humid and warmer climate during the late Atelian. The new findings in regard to the local Caspian climate and environmental evolution support decreased river discharge from the Russian Plain and Siberian Plain as the dominant factor causing the low Caspian sea level stand during the Atelian, although local-regional climate changes might have had an additional influence.